Development of Seribu Rumah Gadang Village as a Tourism Destination - Gisky Andria Putra (Yayasan Cendekiawan Digital Indonesia, 2024)
The Seribu Rumah Gadang village holds immense potential as a tourist destination awaiting development. The primary objective is to foster the continuous progress and growth of the tourism sector in West Sumatra, consequently bolstering the economic landscape. This research adopts a descriptive methodology with a qualitative approach. SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) is employed as the data analysis technique. The findings highlight the necessity of formulating development strategies for the village of a thousand